2012
DOI: 10.1371/journal.pone.0037202
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Regenerative Aspects of Hepatic Mast Cells in Liver Allograft Rejection and Tolerance

Abstract: The precise roles of mast cells in liver allograft rejection and tolerance are still unknown. This study aimed to explore the roles of mast cells in immune regulation and liver regeneration for tolerance induction by using rat models of orthotopic liver transplantation (OLT). Stem cell factor (SCF) and its receptor c-Kit, which are critical to the migration and development of not only stem cells but also mast cells, significantly increased in the tolerogenic livers as compared with rejected livers. The signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 63 publications
2
28
0
3
Order By: Relevance
“…BDL induces ductal proliferation in response to the injured duct(20, 27), and subsequently there is an infiltration of mast cells beginning approximately 2–3 days post-BDL shown in Figure 1. In support of our findings, mast cells are also found in other models of liver injury and repair including following carbon tetrachloride treatment(28), alcohol feeding(29) and during liver regeneration(30). Since mast cells do not mature and differentiate until they reach their tissue of destination, the contents of mast cells may differ between the liver and other organs(25).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…BDL induces ductal proliferation in response to the injured duct(20, 27), and subsequently there is an infiltration of mast cells beginning approximately 2–3 days post-BDL shown in Figure 1. In support of our findings, mast cells are also found in other models of liver injury and repair including following carbon tetrachloride treatment(28), alcohol feeding(29) and during liver regeneration(30). Since mast cells do not mature and differentiate until they reach their tissue of destination, the contents of mast cells may differ between the liver and other organs(25).…”
Section: Discussionsupporting
confidence: 87%
“…It has also been noted that mast cells may play a role in allograft rejection during liver resection or transplantation. In this study, the authors found that a crosstalk exists between mast cells other cells including hepatocytes and induction of mast cell degranulation induces hepatocyte proliferation, thus contributing positively to cellular repopulation and liver regeneration(30). Similar to our findings, mast cells have been noted to increase in number during PSC progression(7, 33) in both rodent models and human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Экспериментальные исследования на моделях спонтанной иммунной толерантности трансплантата печени у мышей показывают, что после трансплантации в донорской печени увеличи-вается количество регуляторных Foxp3+ и γδ Т-кле-ток, что сопровождается увеличением продукции ряда цитокинов, в том числе и TGF-β [8,9]. Кли-нические наблюдения, проведенные Briem-Richter с соавторами [10], выявили тенденцию к повышению уровня TGF-β1 в сыворотке крови реципиентов с хорошей функцией трансплантата печени.…”
Section: Level Of Transforming Growth Factor Beta-1 Relates To Congenunclassified
“…Mast cells play a critical role in the establishment of the organ or tissue transplantation tolerance23. Yet, whether mast cells play a role in regulation of the T helper (Th)2 response is unknown.…”
mentioning
confidence: 99%